Secondary school mathematics, gender, and MUFY math performance : a Sunway campus case study - Tang, Eng Loong * (Sunway University College, 2010)
The purpose of this study is to examine the Malaysian students? performance in Fundamental Mathematics A in the Monash University Foundation Year (MUFY) programme. This study compared Malaysian students? secondary school mathematics background and gender to their performance in MUFY Fundamental Mathematics A. The sample consisted of 125 Malaysian students who took the MUFY Fundamental Mathematics A in January, March, July and August of 2009. The data revealed that the grades of Mathematics at the Sijil Pelajaran Malaysia (SPM) or Malaysian Certificate of Education level were significantly related to the grades of MUFY Fundamental Mathematics A. Furthermore, students with SPM Additional Mathematics performed better than their classmates who did not take the subject in MUFY Fundamental Mathematics A. Also, female students were found to perform better than male counterparts in MUFY Fundamental Mathematics A.